2018
DOI: 10.1155/2018/5192814
|View full text |Cite
|
Sign up to set email alerts
|

Low-Concentration Oxygen/Ozone Treatment Attenuated Radiculitis and Mechanical Allodynia via PDE2A-cAMP/cGMP-NF-κB/p65 Signaling in Chronic Radiculitis Rats

Abstract: Background Oxygen/ozone therapy is a minimally invasive technique for the treatment of radiculitis from lumbar disc herniation. This study aimed at investigating whether intrathecal administration of low-concentration oxygen/ozone could attenuate chronic radiculitis and mechanical allodynia after noncompressive lumbar disc herniation and at elucidating the underlying mechanisms. Methods First, we transplanted autologous nucleus pulposus into dorsal root ganglions to establish chronic radiculitis in rats. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In this preliminary study found that 20 μg/ml of O 3 did not affect the survival of spinal cord cells, whereas ozone concentrations of 30 to 100 μg/ml have been shown to be concentration-dependently neurotoxic to spinal cord neurons [17]. Intrathecal injection of ozone at concentrations of 10, 20, or 30 μg/mL has been shown to significantly reduce mechanical PWT; ozone concentration of 20 μg/ml could not induce nerve damage and was reported to have an anti-inflammatory effect [18]. Ozone at high concentrations Figure 3: BDNF was mainly expressed in the cytoplasm and on the membrane of hippocampal cells in each group, as represented by brown staining.…”
Section: Discussionmentioning
confidence: 97%
“…In this preliminary study found that 20 μg/ml of O 3 did not affect the survival of spinal cord cells, whereas ozone concentrations of 30 to 100 μg/ml have been shown to be concentration-dependently neurotoxic to spinal cord neurons [17]. Intrathecal injection of ozone at concentrations of 10, 20, or 30 μg/mL has been shown to significantly reduce mechanical PWT; ozone concentration of 20 μg/ml could not induce nerve damage and was reported to have an anti-inflammatory effect [18]. Ozone at high concentrations Figure 3: BDNF was mainly expressed in the cytoplasm and on the membrane of hippocampal cells in each group, as represented by brown staining.…”
Section: Discussionmentioning
confidence: 97%
“…Given that EA could influence multiple signaling pathways, including β-endorphins ( Han, 2003 ), cannabinoid CB2 receptors, and adenosine A1 receptor ( Goldman et al, 2010 ), the 5-HT 7 R-associated PKA and ERK 1 / 2 phosphorylation through Gαs-cAMP signaling is likely only one of the key factors involved in EA’s maintenance of antihyperalgesic effects. Moreover, cAMP interacts with several other proteins in addition to PKA and ERK 1 / 2 , including ROS ( Gu et al, 2018 ), NF-κB ( Wang J. et al, 2018 ), and AKAP ( Miyano et al, 2019 ), which might also be involved in the maintenance of the antihyperalgesic effects by EA. Next, we will use naloxone to block opioid receptors, or DPCPX to block A1 receptors, so as to exclude the effect of other factors on EA antihyperalgesia, and then confirm the role of 5-HT 7 R.…”
Section: Discussionmentioning
confidence: 99%
“…including β-endorphins [73], cannabinoid CB2 receptors [74], and adenosine A1 receptor [75], the 5-HT 7 Rmediated PKA and ERK 1/2 phosphorylation through Gαs-cAMP signaling is likely only one of the key factors involved in EA's maintenance of antihyperalgesic effects. Moreover, cAMP interacts with several other proteins in addition to PKA and ERK 1/2 , including ROS [76], NF-κB [77], and AKAP [78], which might also be involved in the maintenance of the antihyperalgesic effects by EA. Next, we will use naloxone to block opioid receptors, or DPCPX to block A1 receptors, so as to exclude the effect of other factors on EA antihyperalgesia, and then con rm the role of 5-HT 7 R.…”
Section: Discussionmentioning
confidence: 99%